A Novel Geospatial Approach for Analyzing Coastal Roadway Vulnerability to Shoreline Changes - Soomin Kim; Jaeyoung Lee; Sungchul Hong (Land, 2025)
Climate changes and coastal development pose growing risks to coastal roadways constructed on flat and low-elevation terrains near retreating shorelines. Although GIS has been widely used for shoreline change analysis and roadway management, significant limitations remain in accurately analyzing shoreline changes relative to roadways and integrating the analysis results into roadway spatial databases in the Geographic Information System (GIS). In this regard, this study proposes a novel geospatial approach that integrates the linear referencing system (LRS) with the vector-offset based analysis method for shoreline change. The LRS, implemented in GIS, defines the specific positions of a roadway using relative distances from predefined referents. Vector offsets, representing the shortest distance and direction from historical shorelines to the roadway, are then employed to analyze shoreline changes. The proposed approach was applied to a coastal roadway experiencing significant shoreline changes driven by climate change and the construction of coastal infrastructure. The results demonstrate the effectiveness of the proposed approach in analyzing shoreline retreat caused by coastal infrastructure development, as well as shoreline accretion following the installation of erosion control structures. These results, which closely reflect the actual erosion pattern, indicate that the proposed approach can effectively support planning for roadway maintenance and reinforcement.